Natural flavones from edible and medicinal plants exhibit enormous potential to treat ulcerative colitis - Qiang Lu; Yuhong Xie; Jingbin Luo; Qihai Gong; Qihai Gong; Cailan Li; Cailan Li; Cailan Li (Frontiers Media S.A., 2023)
Ulcerative colitis (UC) is a chronic aspecific gut inflammatory disorder that primarily involves the recta and colons. It mostly presents as a long course of repeated attacks. This disease, characterized by intermittent diarrhoea, fecal blood, stomachache, and tenesmus, severely decreases the living quality of sick persons. UC is difficult to heal, has a high recurrence rate, and is tightly related to the incidence of colon cancer. Although there are a number of drugs available for the suppression of colitis, the conventional therapy possesses certain limitations and severe adverse reactions. Thus, it is extremely required for safe and effective medicines for colitis, and naturally derived flavones exhibited huge prospects. This study focused on the advancement of naturally derived flavones from edible and pharmaceutical plants for treating colitis. The underlying mechanisms of natural-derived flavones in treating UC were closely linked to the regulation of enteric barrier function, immune-inflammatory responses, oxidative stress, gut microflora, and SCFAs production. The prominent effects and safety of natural-derived flavones make them promising candidate drugs for colitis treatment.